2011
DOI: 10.1007/s10800-011-0320-1
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of Eurofer 97 and ODS-Eurofer alloys compared to traditional stainless steels

Abstract: In the present work, the corrosion resistance of ferritic-martensitic EUROFER 97 and ODS-EUROFER steels was tested in solutions containing NaCl or H 2 SO 4 and KSCN, both at 25°C. The results were compared to those of AISI 430 ferritic and AISI 410 martensitic conventional stainless steels. The as-received samples were tested by electrochemical techniques, specifically, electrochemical impedance spectroscopy, potentiodynamic polarization curves, and double-loop electrochemical potentiokinetic reactivation test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Although the corrosion behavior of ODS alloys is well studied in molten fluoride salts [11], liquid lead [12], lead-bismuth eutectic (LBE) [12], supercritical pressurized water (SCPW) [13], the general corrosion behavior of these group of materials at room temperature is not fully evaluated. Terada et al [14] reported that the corrosion resistance of Eurofer 97 steel decreased with the percentage of oxides dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Although the corrosion behavior of ODS alloys is well studied in molten fluoride salts [11], liquid lead [12], lead-bismuth eutectic (LBE) [12], supercritical pressurized water (SCPW) [13], the general corrosion behavior of these group of materials at room temperature is not fully evaluated. Terada et al [14] reported that the corrosion resistance of Eurofer 97 steel decreased with the percentage of oxides dispersion.…”
Section: Introductionmentioning
confidence: 99%